Elsa Martinelli’s struggle in Kristin Hannah’s The Four Winds - Intan Mandailin Fi Zhilaalil Qur'an; Adeline Grace Marianne Litaay (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
This study deals with how Elsa Martinelli struggles in Kristin Hannah’s The Four Winds. Elsa lives during the Great Depression, the period when the country was in crisis and at war with herself, when millions of people were out of work and even the land seemed to have turned against them. This study uses the pshycological approach that uses references from some journal, thesis, and internet articles. This study uses qualitative descriptive method. The data source in this study is The Four Winds novel written by Kristin Hannah. This study focuses on Elsa Martinelli’s struggle and the impact of the struggle on Elsa Martinelli. Based on this study, Elsa has experienced all her struggle when she decides to move in California. She looks for a better life for her and her children since her husband abandons her. Elsa wants to find a job in foreign country to feed her children, rent a decent place to live for her children and send her children to school. However, it is very difficult to find a job with a suitable salary in such a situation. Keywords: Struggle, Depression, Psychological, Qualitative